Inhibition of oxido-inflammatory and apoptotic pathway is involved in the protective effect of Ginkgo biloba supplement in cyclosporine-A induced vascular dysfunction in Wistar rat - Jerome Ndudi Asiwe; Simon Irikefe Ovuakporaye; Benneth Ben-Azu; Jamil Usman Dauda; Vincent-Junior Onoriode Igben; Endurance Efe Ahama; Ehizokhale Santos Ehebha; Vincent Ugochukwu Igbokwe (Elsevier, 2023)
Background: Cyclosporine (Cs-A), an immunosuppressant drug used to prevent organ rejection in patients receiving organ transplants, has been linked to cardiovascular dysfunction in a growing body of research. Consequently, Cs-A-induced immunosuppression is linked to increased free radical production, inflammatory state, vascular remodeling and endothelial impairment leading to cardiovascular dysfunction. Whether Ginkgo biloba supplement (GBS), a Chinese herbal supplement that boosts antioxidants, will restore vascular functions in Cs-A-induced vascular dysfunction remains unknown. Therefore, this study examined in Wistar rats the protective effects of GBS on Cs-A-induced vascular dysfunction. Methods: Animals were randomly selected into four groups and treated as follows; Group 1, 2, 3 and 4 received distilled water (10 ml/kg) for 15 days, Cs-A (25 mg/kg) for 15 days, GBS (50 mg/kg) for 15 days and Cs-A with GBS for 15 days respectively. All treatment was done intraperitoneal and tissues were harvested, homogenised and the supernatant was used for the biochemical assay. Results: Our results revealed that GBS significantly suppressed Cs-A-induced oxido-inflammatory and apoptotic pathways evidenced by increased CAT, SOD, GSH levels and decreased MDA, IL-6, TNF-α and caspase-3 levels. Also vascular tone was improved by regulating the switch between vasoconstriction and vasodilation via normalization of endothelial Nitric oxide and endothelin-I signaling. Hyperactivity of Na-K ATPase was normalised by GBS leading to improved structural and histomorphological integrity. Conclusion: Overall finding of this study suggest that GBS improves structural integrity in Cs-A-induced endothelial dysfunction via modulation of oxido-inflammatory and apoptotic mediators